UV-induced inactivation and mutation-induction in a new two-component heterokaryon (59) homozygous for the excision-repair deficient mutant uvs-2 - F. J. de Serres; N. J. Berheim (Fungal Genetics Reports, 1980)
UV-induced inactivation and mutation-induction in a new two-component heterokaryon (59) homozygous for the excision-repair deficient mutant uvs-2.